Serial membrane sweeping at term in planned vaginal birth after cesarean a randomized controlled trial - Hamdan, M.; Sidhu, K.; Sabir, N.; Omar, S.Z.; Tan, P.C. (2009)
OBJECTIVE: To estimate the effect of serial membrane sweeping on the onset of labor in women who planned vaginal birth after cesarean (VBAC). METHODS: Women at term with one transverse lower segment cesarean delivery who were suitable for and who planned VBAC were approached to participate. Participants were randomly assigned to weekly membrane sweeping or weekly vaginal assessment for Bishop score until delivery. Participants and delivery providers were blinded to the allocated treatment. Standard obstetric care was given to all participants. The primary outcome was onset of labor which was defined as the presence of spontaneous regular and painful contractions that cause cervical dilation to at least 3 cm or prelabor rupture of membranes. Secondary outcomes included induction of labor and repeat cesarean delivery. RESULTS: One hundred eight women were randomly assigned to membrane sweeping and 105 to control. The spontaneous labor rate was 78.5 compared with 72.1 (relative risk RR 1.1, 95% confidence interval CI 0.9-1.3; P=.34), the induction of labor rate was 12.1% compared with 9.6% (RR 1.3, 95% Cl 0.6-2.8; P=.66), and the all-cause cesarean delivery rate was 40.2% compared with 44.2% (RR 0.9, 95% Cl 0.7-1.2; P=.58) for the membrane sweeping and control groups, respectively. Gestational age at delivery (mean +/- standard deviation) of 39.6 +/- 1.0 weeks for the membrane sweeping group compared with 39.6 0.9 weeks for the control group (P=.84) was no different. CONCLUSION: Serial membrane sweeping at term in women who planned VBAC has no significant effect on the onset of labor, pregnancy duration, induction of labor, or repeat cesarean delivery.